Enhancing Rural Biology Instruction through Technology Integration: The Roles of TPACK, Situated Learning, Funds of Knowledge, Digital Literacy, Professional Development, and Institutional Support - Bullecer, Kayco; Balbuena, Abegail; Benitez, Flomena; Besonia, Louielyn; Bisaya, Patrick (JPAIR Multidisciplinary Research, 2026)
The integration of technology into science education has become increasingly vital in addressing the challenges of teaching abstract concepts in Grade 10 Biology, particularly within rural contexts where resources and cultural assets shape learning experiences. The main objective of this study is to synthesize literature on six interrelated hypotheses: the role of teachers’ Technological Pedagogical Content Knowledge (TPACK), the influence of Situated Learning Theory on student engagement, the moderating effect of Funds of Knowledge (FoK), the strengthening impact of Collaborative Professional Development (CPD), the mediating role of student digital literacy, and the reinforcing function of institutional support and policy frameworks in sustaining technology integration. Employing a narrative literature review methodology, peer reviewed articles, books, and indexed conference proceedings from 1991 to 2025 were analyzed thematically to identify convergences, divergences, and gaps. Significant results reveal that higher levels of TPACK enable effective integration of digital tools, contextualized practices framed by Situated Learning Theory enhance engagement, FoK ensures cultural relevance, CPD builds teacher capacity, digital literacy mediates achievement gains, and institutional support sustains long term integration. In conclusion, the study demonstrates that effective and sustainable technology integration in rural biology classrooms requires a holistic approach that combines teacher expertise, student capacities, community assets, and systemic supports.